DUKUNGAN SOSIAL KELUARGA DAN HARDINESS DENGAN PROBLEM FOCUSED COPING PADA MAHASISWA - Firda Amelia Prayogo; Wiwik Sulistiani; Puri Aquarisnawati (Fakultas Psikologi Universitas Hang Tuah, 2021)
Currently the Covid-19 pandemic is causing many impacts and problems one of them is in the educational especially on students. Problem focused coping is more appropriate to resolve the problem. This study aims to determine the relationship between family social support and problem focused coping and the relationship between hardiness and problem focused coping in students. The samples in this study totaled 360 respondents. The sampling technique used quota sampling. The study used three scales, family social support, hardiness and focused coping problems. The approach used was by the survey method and using the product moment correlation test. The results of the first hypothesis test were rejected (significant standard 0.052 is more than 0.05) meaning that there was no relationship between family social support and focused coping problems. The results of the second hypothesis test were accepted (significant standard 0.012 is less than 0.05) meaning that there was a positive relationship between hardiness and focus-coping problems in students.